"Calm Down, " "Cheer Up": How Age Influences the Way We Manage Emotion in Social Partners. (February 2021) - Jarman, Ruth E.; Windsor, Tim D.
This study examines how individuals (regulators) manage emotion in their social partners (targets) and whether the age of the regulator or the age of the target influences extrinsic emotion regulation strategy preference. An online questionnaire was used to assess extrinsic emotion regulation among 580 participants aged 18–87 years ( M = 50.04, SD = 18.13). Participants (regulators) indicated the extent to which they would be likely to use different strategies when interacting with a younger or older target who was upset. Results of multi-level modeling showed that older regulators endorsed less use of situation modification than younger regulators, but age differences in regulators' use of other strategies were not significant. After adjustment for relationship-specific covariates, regulators endorsed less use of attentional deployment and cognitive change, for older targets than younger targets. Results are discussed in the context of lifespan perspectives on social behavior and emotion regulation.